Diversity and Species Composition of Odonates (Insecta: Odonata) of Hutan Lipur Soga Perdana, Batu Pahat, Johor, Malaysia: A Green Lung - Abdul Aziz, Muhamad Amirul Ashraf; Mohamed, Maryati (Journal of Science and Technology, 2018)
In Malaysia, Odonates have been used widely in the assessment of water quality. This study is part of an effort to prepare a baseline data for the state of Johor, where development is happening at a fast rate which in turn could affect the water quality. Hutan Lipur Bukit Soga Perdana is a green lung for Batu Pahat which is considered as the second largest industrial town in Malaysia. Opportunistic sampling using sweep nets along 1 km line transect was conducted for a total of six days. Twenty-two species of Odonata belonging to 17 genera and seven families were recorded. Among the seven families, the most species-rich were Libellulidae (12 species) followed by Coenagrionidae and Platycnemididae (three species) while Gomphidae, Platystictidae, Devadattidae and Euphaeidae represented by single species. Drepanosticta fontinalis, a damselfly endemic to Peninsular Malaysia was collected. The abundance of the endemic Drepanosticta fontinalis was 10.3% from a total of 126 individuals. Tyriobapta torrida (15.9%) was found to be the most abundant species found followed by Prodasineura notostigma (12.7%) and Neurothemis fluctuans (11.9%). The data were further analysed by using Shannon-Wiener Species Diversity Index giving a value of 2.63 indicating a moderate diversity. Simpson’s Evenness is 0.91 indicating a high evenness in the distribution of Odonates. Since the forest gains high public interest in Batu Pahat and Odonates are visible and useful insects, more studies could be done, and the data could be transferred to the public as a model for biodiversity and conservation.